2007
DOI: 10.1002/humu.20618
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes-associated fatty acid binding protein 2 promoter haplotypes are differentially regulated by GATA factors

Abstract: The human intestinal fatty acid binding protein 2 (FABP2) mediates fat absorption by binding and intracellular trafficking of long-chain free fatty acids. Studies with knockout mice and association analysis of polymorphisms revealed that FABP2 is a susceptibility gene for type 2 diabetes (noninsulin dependent diabetes mellitus [NIDDM]) and related traits. Relevant FABP2 promoter polymorphisms c.-80_-79insT (rs5861422), c.-136_-132delAGTAG (rs5861423), c.-168_-166delAAGinsT (rs1973598), c.-260G>A (rs6857641), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…(2007) have shown that this variation interacts with the association of the human FABP2:p.Ala54Thr polymorphism. Very recently, Klapper et al . (2008) have shown that GATA factors regulate this promoter variant‐specific transcription rate in the human FABP2 gene, providing a molecular basis for the expression differences among promoter genotypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2007) have shown that this variation interacts with the association of the human FABP2:p.Ala54Thr polymorphism. Very recently, Klapper et al . (2008) have shown that GATA factors regulate this promoter variant‐specific transcription rate in the human FABP2 gene, providing a molecular basis for the expression differences among promoter genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Damcott et al (2003) and Formanack and Baier (2004) found that nucleotide variation in the promoter of the human FABP2 gene influences its transcription rate and, more recently, Helwig et al (2007) have shown that this variation interacts with the association of the human FABP2:p.Ala54Thr polymorphism. Very recently, Klapper et al (2008) have shown that GATA factors regulate this promoter variant-specific transcription rate in the human FABP2 gene, providing a molecular basis for the expression differences among promoter genotypes. Thus, although the estimated QTL position suggests that the causal factor would be located within the S0144-SW61 marker interval, it cannot be ruled out that a polymorphism in the promoter region of the porcine FABP2 gene, rather than a structural mutation, could be involved in the QTL.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, we have shown that FABP2 is regulated by HNF-4α and GATA factors (Klapper et al, 2007b), that are key regulators of intestinal differentiation processes. As described on liver and intestinal expressed fatty acid binding protein FABP1, LPH and SI promoters, HNF-1α co-operates with these factors (Krasinski et al, 2001;Boudreau et al, 2002;van Wering et al, 2002;Divine et al, 2004;van Wering et al, 2004;Rowley et al, 2006) and is also involved in developmental expression of intestinal genes (Bosse et al, 2007).…”
Section: Hnf-1α Activates Fabp2 Promoter In Caco-2 and Hela Cellsmentioning
confidence: 99%
“…In view of the normative postulate outlined above, we would rather maintain that basic research in nutritional science should address all biopsychosocial aspects of nutrition [17]. Examples of basic research oriented questions in nutritional science may be: Biological: What is the role of the intestinal fatty acid binding protein in fat assimilation [81] and how its regulation can be characterized [82][83][84][85]? Psychological: How do cognitive conditions influence the selection of food [86]?…”
Section: Nutritional Science -Basic Science or Applied Science?mentioning
confidence: 99%